The Urgency of Using Artificial Intelligence (AI) In Public Services - Mulyasari, Septy Dwi Diantika; Jaya Wardana, Dodi (Jurnal Daulat Hukum, 2025)
The rapid development of information technology has driven transformation in various sectors, including public services. Artificial Intelligence (AI) is present as an innovative solution to improve the efficiency, accuracy, and quality of services provided by government agencies. This article discusses the urgency of implementing AI in public services as a strategic step to realize responsive, transparent, and data-driven governance. The use of AI can accelerate administrative processes, minimize human error, and increase public satisfaction with government services. This research uses literature as the primary method to examine various implementations of AI in the public sector both nationally and globally. The results of the study indicate that the application of AI not only supports bureaucratic efficiency but also serves as a key driver in realizing the digital transformation of government. Therefore, adaptive policies, clear regulations, and strengthening human resource capacity are needed so that the implementation of AI in public services can run optimally and sustainably.